2017
DOI: 10.1055/s-0037-1605559
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characterization of Hypoesthesia in the Distribution of the Infrapatellar Branch of the Saphenous Nerve after Anterior Cruciate Ligament Reconstruction: A Prospective Study of Patient-Reported Numbness

Abstract: The purpose of this study was to determine the incidence of patient-reported numbness following anterior cruciate ligament reconstruction (ACLR), if postoperative numbness dissipates with time, and how the graft type affects numbness severity. A total of 218 patients undergoing ACLR were prospectively enrolled. At 6 weeks, 6 months, and 1 year postoperatively, patients completed a questionnaire assessing numbness severity and location. Each time, patients rated their sensory deficit from 0 to 10 (0 = no defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…1, area A3 in Cohen et al, ). Dermatome maps vary considerably in this location (Cohen et al, ;Ladak et al, 2014;Standring S, 2016). Retrospective review demonstrated iliacus (supplied by proximal femoral nerve) and gluteal muscle (supplied by superior and inferior gluteal nerves) hypertrophy (i.e., extra-territorial overgrowth).…”
mentioning
confidence: 87%
“…1, area A3 in Cohen et al, ). Dermatome maps vary considerably in this location (Cohen et al, ;Ladak et al, 2014;Standring S, 2016). Retrospective review demonstrated iliacus (supplied by proximal femoral nerve) and gluteal muscle (supplied by superior and inferior gluteal nerves) hypertrophy (i.e., extra-territorial overgrowth).…”
mentioning
confidence: 87%
“…The classical teaching about CNF covered by cutaneous nerves at the anteromedial limb in most cases is limited by several factors. A knowledge of the CNF at the anteromedial lower limb is based on anatomical textbooks (Ladak, Tubbs, & Spinner, 2014; Standring & Gray, 2008) or observational studies of hypoesthesia after several surgeries (Cohen et al, 2017; Tanavalee, Limtrakul, Veerasethsiri, Amarase, & Ngarmukos, 2016). These descriptions lack differentiation between distinct cutaneous nerve branches (e.g., medial or intermediate femoral cutaneous nerves), do not describe the possible overlap of CNF, and do not distinguish the possible variabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical approaches to the anteromedial knee may be complicated by iatrogenic injury to the IBSN, which has been reported after total knee arthroplasty (TKA), arthroscopic knee surgery, anterior cruciate ligament reconstruction, and surgical meniscectomy [3][4][5][6][7][8][9][10]. Patients typically complain of numbness, a burning sensation, and hypersensitivity in the cutaneous distribution of the IBSN.…”
Section: Introductionmentioning
confidence: 99%